G325(P) Understanding uptake of immunisations in travelling and gypsy communities. (27th April 2016) - Bedford, H; Beach, H; Cheater, F; Condon, L; Crocker, A; Dyson, L; Emslie, C; Kerr, S; Kemsley, P; Ireland, L; Lewis, H; Mytton, J; et al.
Abstract : Aims: To investigate the barriers and facilitators to acceptability and uptake of immunisation among Gypsy/Traveller communities in the UK. Methods: We interviewed 174 Gypsy/Travellers from five communities: Romanian/Slovakian Roma, English Gypsy, Irish Travellers, English Roma, Scottish Showpeople, in four UK cities: Interviews gathered views about the influences on their immunisation behaviours (childhood, adult flu and pertussis vaccines) and ideas for improving uptake in their community. Interview data were analysed using the framework approach. The Social Ecological Model provided the theoretical framework. Results: General acceptance of immunisation based on social norms and trust in health professionals was expressed by approximately half of the participants from the English Roma and London Irish Traveller communities in two cities; three quarters of the English Gypsy/Irish Traveller community and Scottish Showpeople; and almost all of the Romanian/Slovakian Roma participants. Concerns about specific vaccines were evident for particular communities e.g. pertussis vaccine in pregnancy for the English/Irish Traveller community in one city, MMR for the Scottish Showpeople. A belief that having the HPV vaccination would imply that Traveller girls are promiscuous was evident for a minority of Travellers in four communities (not Scottish Showpeople). Romanian/Slovakian Roma communities identified language barriers to accessing immunisation services and low literacy across all communities resulted in people being unable to read immunisation leaflets or letters/texts about appointments and struggling to make sense of conversations with health professionals. Relationships with health professionals appeared to be very important. Recall and reminder systems (letters, texts, phone calls) were seen as effective for the majority of participants including those who regularly travel. Most did not appear to have problems with attending appointments for immunisations although some talked about the difficulty of registering with a GP practice without a fixed address and being unable to get an appointment within two weeks. Conclusion: Although these Travellers' accounts of the barriers and facilitators to immunisation have consistency with the wider population, there are some important differences between communities. Immunisation services need to be aware of Gypsy/Traveller communities in their area and tailor services accordingly.